Effect of five diets with different neutral detergent fibre and starch ratios on productive performance, ingestive ratio, and weight of digestive organs in guinea pigs (Cavia porcellus) - Paredes A., Manuel (2021)
The aim of this study was to determine the effects of the ratio of neutral detergent fibre (NDF) and starch in the diet on productive performance, ingestive ratio and weight of the digestive organs of guinea pig (Cavia porcellus). Five isonitrogenous diets were prepared varying the NDF:starch ratio (PFA): 8.1, 3.5, 2.0, 1.3, and 0.8. In total, 160 28-day-old guinea pigs fed for seven weeks were used. The weight gain and the feed conversion index in the PFA 2.0 and PFA 1.3 groups were better than the other groups (p<0.05), together with a higher carcass performance (p<0.05). The weight gain in PFA 3.5 was greater than in the PFA 8.1 and PFA 0.8 groups (p<0.05). The relative intake of dry matter (DM) and the intake of NDF in the PFA 8.1 group was the highest; however, the digestible energy intake in PFA 8.1 was the lowest (p<0.05). Cecum weight was higher in PFA 8.1, PFA 3.5 and PFA 2.0 than in PFA 1.3 and PFA 0.8 (p<0.05). The DM intake in PFA 0.8 was the lowest. The results indicate that the optimal NDF:starch ratio in growing guinea pig diets is between 1.3 and 2.0.